Efektivitas Kegiatan Kelompok Kerja Kepala Sekolah Dasar Negeri dalam Penyusunan Rencana Kerja di Desa Lumpatan Kabupaten Musi Banyuasin - Khodijah, Siti (Yayasan Sembilan Pemuda Indonesia, 2021)
The primary objective of this study is to determine the effectiveness of the Public Elementary School Principal Working Group's activities in Lumpatan Village, Musi Banyuasin Regency. Qualitative analysis was used in this study. Data is collected in natural settings (natural conditions), using primary data sources, and relying heavily on observation, interviews, and documentation. The findings revealed that human resources lacked performance and managerial competence in supporting the preparation of a work plan for activities of the Principal's Working Group, as well as insufficient facilities and infrastructure; the preparation of School Principal Working Group Activity Plans and education and training indicators were not running effectively; and the principal's low motivation had a negative impact.